Is quality certification in fruit and vegetable production a market-driven choice in Greece? - Dimitrios Tselempis; Philippos Karipidis; Alexandra Pavloudi; Anastasios V. Semos (Agricultural and Food Economics, 2015)
This study examines whether the implementation of a quality management system (QMS) and the choice of a certain quality assurance scheme (QAS) were decided as responses by fruit and vegetable producers to market conditions, separating certification decisions into two components. A survey study is conducted and two discrete choice models are estimated: ordered logit for the implementation of QMS and binary probit for the choice of QAS. It is found that the buyers' demand for certification and the efforts of farmers to differentiate their products from others in an area that may present local quality problems lead farm businesses to accelerate QMS implementation. Regarding the choice of a private QAS, it is a market-driven decision. The conclusion is that certifications are characterised by a market-driven approach and the increased interest in certified products can lead to the diffusion of certification. Because the absence of information provision and the controls exerted by public authorities have an impact on QMS implementation, the diffusion of certification depends also on public policy measures, indicating the crucial role of a public policy mix properly designed to promote certification.
Keywords: 330; Market; Certification; Decisions; Standards; Quality systems; Policy